PEMANFAATAN SEMPADAN TUKAD BINDU SEBAGAI RUANG KREATIVITAS GENERASI MUDA DI KOTA DENPASAR - Kadek Ari Darmawan; Komang Wirawan; I Gusti Putu Anindya Putra (Pranatacara Bhumandala: Jurnal Riset Planologi, 2021)
Denpasar City is the capital city of Bali Province, with various watersheds that cross Denpasar City. Judging from this, the Denpasar City Government is committed to utilizing the river border into a recreation space as a form of creativity space. By involving the role of the younger generation to use Tukad Bindu as a creative space that changes the face of the river which is seen as slum, a lot of garbage, a place as a washing location for the local community, and has the creepy impression of "Tenget" into a recreation area while maintaining the sustainability of the river. The background of this research is to identify how the arrangement of Tukad Bindu into a recreational area as a form of creative space for the younger generation in Denpasar City and can find out the impact of structuring Tukad Bindu into a recreation area as a creative space for the younger generation in Denpasar City. With qualitative descriptive research methods, using observations or observations, interviews, and documents. These methods are combined to describe what happened and obtain facts related to identifying the potential of nature, location, culture, human resources using qualitative descriptive analysis. The expected result is a model of structuring the area through maps such as conservation areas and recreation areas and can see the impacts such as environmental impacts, economic impacts and socio-cultural impacts.